Topoisomerase-specific drug sensitivity in relation to cell cycle progression. - Chow, K C (1987)
The nuclear enzyme DNA topoisomerase II catalyzes the breakage and resealing of duplex DNA and plays an important role in several genetic processes. It also mediates the DNA cleavage activity and cytotoxicity of clinically important anticancer agents such as etoposide. We have examined the activity of topoisomerase II during the first cell cycle of quiescent BALB/c 3T3 cells following serum stimulation. Etoposide-mediated DNA break frequency in vivo was used as a parameter of topoisomerase II activity, and enzyme content was assayed by immunoblotting. Density-arrested A31 cells exhibited a much lower sensitivity to the effects of etoposide than did actively proliferating cells. Upon serum stimulation of the quiescent cells, however, there was a marked increase in drug sensitivity which began during S phase and reached its peak just before mitosis. Maximal drug sensitivity during this period was 2.5 times greater than that of log-phase cells. This increase in drug sensitivity was associated with an increase in intracellular topoisomerase II content as determined by immunoblotting. The induction of topoisomerase II-mediated drug sensitivity was aborted within 1 h of exposure of cells to the protein synthesis inhibitor cycloheximide, but the DNA synthesis inhibitor aphidicolin had no effect. In contrast to the sensitivity of cells to drug-induced DNA cleavage, maximal cytotoxicity occurred during S phase. A 3-h exposure to cycloheximide before etoposide treatment resulted in nearly complete loss of cytotoxicity. Our findings indicate that topoisomerase II activity fluctuates with cell cycle progression, with peak activity occurring during the G2 phase. This increase in topoisomerase II is protein synthesis dependent and may reflect a high rate of enzyme turnover. The dissociation between maximal drug-induced DNA cleavage and cytotoxicity indicates that the topoisomerase-mediated DNA breaks may be necessary but are not sufficient for cytotoxicity and that the other factors which are particularly expressed during S phase may be important as well.